2020
DOI: 10.3390/ma13061334
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Synovial Fluid Composition, Speed and Load on Frictional Behaviour of Articular Cartilage

Abstract: Articular cartilage ensures smooth motion of natural synovial joints operating at very low friction. However, the number of patients suffering from joint diseases, usually associated with cartilage degradation, continuously increases. Therefore, an understanding of cartilage tribological behaviour is of great interest in order to minimize its degradation, preserving the reliable function of the joints. The aim of the present study is to provide a comprehensive comparison of frictional behaviour of articular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Though the samples were removed from different animals, the values and trends of CoF were comparable; nevertheless, the deviation of CoF depended on the combination of friction samples, testing conditions, etc. A rise in CoF trends, which was shown in this study, has been known from other publications [38,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60], and the values of CoF were comparable depending on the processing conditions, configuration of specimens, and lubricants. A comparison of particle count trends showed that the ϒ-globulin protein clusters were wiped off faster from the contact than the albumin; thus, the lubrication film was formed especially by albumin clusters.…”
Section: Friction and Lubrication In Cartilage Contactsupporting
confidence: 87%
See 2 more Smart Citations
“…Though the samples were removed from different animals, the values and trends of CoF were comparable; nevertheless, the deviation of CoF depended on the combination of friction samples, testing conditions, etc. A rise in CoF trends, which was shown in this study, has been known from other publications [38,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60], and the values of CoF were comparable depending on the processing conditions, configuration of specimens, and lubricants. A comparison of particle count trends showed that the ϒ-globulin protein clusters were wiped off faster from the contact than the albumin; thus, the lubrication film was formed especially by albumin clusters.…”
Section: Friction and Lubrication In Cartilage Contactsupporting
confidence: 87%
“…The samples were removed by a hollow punch with an internal diameter of 9.7 mm and stored in phosphate-buffered saline (PBS), deeply frozen (−20 • C), and defrosted immediately before the experiments. The same sampling procedure was used in [55,58] and verified in [64,65]. The sampling process is shown in Figure 4.…”
Section: Specimens and Lubricantsmentioning
confidence: 99%
See 1 more Smart Citation
“…These model fluids were prepared with concentrations of components at real physiologic values, as evaluated by Galandakova et al [25]. In particular, the three types of model fluids are the mimic of SF of healthy or physiologic joint (SF1), SF of total joint replacement (SF2) and SF within a joint with osteoarthritis (SF3) [25,29]. In the model fluids, the concentrations of albumin, γ-globulin, HA and phospholipids were maintained within the range observed in human joints, as described in Table 1.…”
Section: Model Fluid Lubricantsmentioning
confidence: 99%
“…Although the molecular weight of HA has a vital impact on its rheological properties, the HA molecular weight and its coefficient of friction had no mutual dependency [44]. Also, only a limited effect on friction was found when protein-based lubricants were applied varying the fluid constituent concentration in the range corresponding to physiologic and osteoarthritic SF [29]. A dependence between the coefficient of friction for model fluids, proteins and HA with chemical changes of Co-Cr-Mo could not be identified.…”
Section: Coefficient Of Friction Analysismentioning
confidence: 99%